2010
DOI: 10.1007/s00268-009-0370-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Outcome of Total Thyroidectomy in Young Patients with Multiple Endocrine Neoplasia Type 2: A Nationwide Long‐Term Follow‐up Study

Abstract: BackgroundMultiple endocrine neoplasia type 2 (MEN 2) is caused by a RET mutation in chromosome 10. All MEN 2 patients develop medullary thyroid carcinoma (MTC). The age-related risk of MTC is associated with the type of RET mutation. Our aim was to identify prognostic factors associated with recurrent MTC in MEN 2 patients.MethodsIn a nationwide case–control study, all patients who underwent total thyroidectomy in the Netherlands under the age of 20 years were classified into standard (1), high (2), or very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…Notably, to our knowledge, this is the first time that a study has shown this result. Few studies examined the long-term outcome after thyroidectomy in MEN2A patients (19,20,21,22); moreover, only one of them (21) analysed differences in the long-term outcome between the different variants of codon 634 mutations, and that study did not find any differences. This previous study had analysed a smaller number of patients than our investigation, and patients were below the age of 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, to our knowledge, this is the first time that a study has shown this result. Few studies examined the long-term outcome after thyroidectomy in MEN2A patients (19,20,21,22); moreover, only one of them (21) analysed differences in the long-term outcome between the different variants of codon 634 mutations, and that study did not find any differences. This previous study had analysed a smaller number of patients than our investigation, and patients were below the age of 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Schreinemakers et al conducted a case-control study to identify prognostic factors associated with recurrent MTC. 79 A total of 93 MEN2 patients were identified as RET-mutation carriers who underwent total thyroidectomy before 20 years of age. Disease-free patients were compared to those with recurrent disease.…”
Section: Cancermentioning
confidence: 99%
“…Similarly, Sanso et al [9] reported a case of MTC discovered in a 17-month-old patient with a codon 634 mutation. In Schreinemakers et al’s [10] publication which included 62 patients with the mutation, the earliest age of MTC was 1.25 years.…”
Section: Discussionmentioning
confidence: 99%